The Effectiveness of Family Support on Utilizing Basic Immunization Services In Posyandu Bambu Village Mamuju - I Kadek Dwi Swarjana; Dewarawati Patandean (International Journal of Nursing and Health Services (IJNHS), 2021)
Efforts to prevent the transmission and transmission of dangerous infectious diseases in children, especially those under five years of age. Immunization is a form of health intervention that is very effective in reducing infant and under-five mortality rates. However, the achievement of the global target of 1 in 5 children in the world is recorded that they have not received routine immunization. This study aims to determine the description of family support by utilizing basic immunization service facilities. Methods: This study used an analytic survey design with a cross sectional study approach. Sampling by purposive sampling. The data collection technique was done by using a questionnaire. The sample in this study were 100 subjects who met the inclusion criteria. Results: The study shows that from the statistical analysis test using the SPSS version 16.0 program, it shows that 51.0% of the mother's family support is good, 37.0% is sufficient. Meanwhile, using posyandu service facilities showed 72.0%. Conclusion: This shows that there is a relationship between family support and the use of basic immunization services at posyandu with a significance level of ? = 0.031.